2005
DOI: 10.1007/s10570-004-6092-6
|View full text |Cite
|
Sign up to set email alerts
|

Barrier and mechanical properties of modified starches

Abstract: The study addressed starch-based coatings on paper and fabrics. Coated materials and free starch films containing different amounts of a well-established plasticizer (glycerol) or potential plasticizer (mainly polyols) were tested with respect to water vapour permeance (WVPe), water vapour permeability (WVP), glass transition temperature (T g ), and mechanical strength (tensile tests). Both normal and high-amylose potato starch were used. These starches were modified by (a) oxidation, (b) oxidation and hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
3
35
0
Order By: Relevance
“…The effect of different plasticizers that coexist in a starch film depends on their relative concentration. 5 Jansson and Järnström 6 showed that WVP was lower for hydroxypropylated starch films plasticized with glycerol than with other plasticizers such as alkyl polyglucoside. Furthermore, they showed that the glass transition temperature (Tg) decreased as the glycerol content in the free films increased, all in accordance to theoretical values of Tg.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of different plasticizers that coexist in a starch film depends on their relative concentration. 5 Jansson and Järnström 6 showed that WVP was lower for hydroxypropylated starch films plasticized with glycerol than with other plasticizers such as alkyl polyglucoside. Furthermore, they showed that the glass transition temperature (Tg) decreased as the glycerol content in the free films increased, all in accordance to theoretical values of Tg.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydrophilic character of biopolymers, they must generally be combined with hydrophobic materials, such as fatty acids and waxes. Two primary preparation methods exist for lipid based bio-films; emulsion films and bilayer films, the latter being a better barrier for oxygen and water vapour [34][35][36][37][38][39].…”
Section: Biopolymer Films and Coatingsmentioning
confidence: 99%
“…The polysaccharide polymers in particular will be highlighted in this review. Biopolymer films for use as packaging materials based on starch [33][34][35][36][37][38], chitosan [57][58], cellulose derivatives [63,[77][78][79][80][81][82], and hemicelluloses [43][44][45][46] are described in detail in the literature. Bio-based materials have also been used, for example, in composite formulations (e.g., starch/low-density polyethylene (LDPE) blends) [24,25].…”
Section: Biopolymer Films and Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of a plasticizer such as glycerol can improve the mechanical properties, but at high levels, the plasticizer can increase the mobility of amylose chains at a degree which leads to increased crystallinity. 88 The effect of the formation of a close-packed structure with linear amylose on the barrier properties was illustrated by Jansson and Järnström,96 who showed that the water vapour permeability of a high amylose starch fi lm was about 10 times lower than for that of a normal potato starch.…”
Section: Biomaterialsmentioning
confidence: 99%